Acute exercise induces distinct quantitative and phenotypical T cell profiles in men with prostate cancer - Hanson, Erik D.; Sakkal, Samy; Bates-Fraser, Lauren C.; Que, Shadney; Cho, Eunhan; Spielmann, Guillaume; Kadife, Elif; Violet, John A.; Battaglini, Claudio L.; Stoner, Lee; Bartlett, David B.; McConell, Glenn K.; et al. (Frontiers in Sports and Active Living, 2023)
Background: Reduced testosterone levels can influence immune system function, particularly T cells. Exercise during cancer reduces treatment-related side effects and provide a stimulus to mobilize and redistribute immune cells. However, it is unclear how conventional and unconventional T cells (UTC) respond to acute exercise in prostate cancer survivors compared to healthy controls. Methods: Age-matched prostate cancer survivors on androgen deprivation therapy (ADT) and those without ADT (PCa) along with non-cancer controls (CON) completed ~45 mins of intermittent cycling with 3 min at 60% of peak power interspersed by 1.5 min of rest. Fresh, unstimulated immune cell populations and intracellular perforin were assessed before (baseline), immediately following (0h), 2h, and 24h post-exercise. Results: At 0h, conventional T cell counts increased by 45-64% with no differences between groups. T cell frequency decreased by -3.5% for CD3+ and -4.5% for CD4+ cells relative to base at 0h with CD8+ cells experiencing a delayed decrease of -4.5% at 2h with no group differences. Compared to CON, the frequency of CD8+CD57+ cells was -18.1% lower in ADT. Despite a potential decrease in maturity, ADT increased CD8+perforin+ GMFI. CD3+V7.2+CD161+ counts, but not frequencies, increased by 69% post-exercise while CD3+CD56+ cell counts increased by 127% and were preferentially mobilized (+1.7%) immediately following the acute cycling bout. There were no UTC group differences. Cell counts and frequencies returned to baseline by 24h. Conclusion: Following acute exercise, prostate cancer survivors demonstrate normal T cell and UTC responses that were comparable to CON. Independent of exercise, ADT is associated with lower CD8+ cell maturity (CD57) and perforin frequency that suggests a less mature phenotype. However, higher perforin GMFI may attenuate these changes, with the functional implications of this yet to be determined.